The effect of stromal components on the modulation of the phenotype of human bronchial epithelial cells in 3D culture - Pageau, Steven C.; Sazonova, Olga V.; Wong, Joyce Y.; Soto, Ana M.; Sonnenschein, Carlos (Biomaterials, 2011)
The stroma plays an important role in the development and progression of human diseases. Pulmonary diseases such as asthma, fibrosis and cancer are thought to be the result of altered communications between the epithelial and stromal tissue compartments. In order to study these epithelial–mesenchymal interactions, we developed a three dimensional (3D) in vitro model of the human airway that mimics bronchial morphology and function. This model consists of a type-I collagen matrix, normal human fetal lung fibroblasts (IMR-90) or primary human adult lung cancer-associated fibroblasts (LuCAFs), and a surface epithelium of normal human bronchial epithelial cells (HBECs). When cultured at an air–liquid interface (ALI), the epithelial component generated a well-differentiated pseudo-stratified bronchial epithelium that contained basal, ciliated, and non-ciliated (secretory) epithelial cells. IMR-90 and LuCAFs differentially altered the phenotype of HBECs in distinct ways. While IMR-90 permitted HBECs to form a typical respiratory surface epithelium, LuCAFs promoted HBECs to invade the collagen gel forming both epithelial nodules and cysts, suggesting that LuCAFs may alter the HBEC phenotype by modifying biomechanical signals conveyed through the extracellular matrix (ECM). Furthermore, LuCAFs secreted soluble factors that induced HBECs to express genes associated with immune responses, apoptosis, mitosis, cell survival, differentiation and cancer.